Effectiveness of Drug Booklet Administration on Hypertensive Patients' Compliance Levels at the Central Hospital of Buton Regency - Adriani; Muhammad Tasjiddin Teheni; Sitti Alfyanita Ilham (Journal of Health Science and Pharmacy, 2026)
Background: Hypertension is defined by a systolic blood pressure of 140 mmHg or higher and a diastolic blood pressure of 90 mmHg or higher. This condition is associated with an increased risk of damage to vital organs, including the heart and the brain, potentially leading to cerebrovascular accidents. Medication adherence is crucial for managing hypertension and preventing complications. Objectives: The aim of this study was to evaluate the effect of educational booklet media on medication adherence among hypertensive patients receiving treatment at the Central Buton Regional General Hospital. Methods: This study employed a one-group pre-and post-test design using a pre-experimental method. The research focused on hypertensive patients and utilized the Morisky Medication Adherence Scale (MMAS-8) questionnaire to measure medication adherence. Qualitative research methods were applied to assess the impact of the educational booklet on patient behavior. Results: The results indicated that the provision of medication instructions through educational booklets significantly influenced the adherence of hypertensive patients at the Central Buton Regional General Hospital. Prior to receiving the educational booklet, 5 respondents (7.7%) demonstrated high adherence, 12 respondents (18.5%) showed moderate adherence, and 48 respondents (73.8%) exhibited low adherence. After the intervention, 8 respondents (12.3%) exhibited high adherence, 21 respondents (32.3%) displayed moderate adherence, and 36 respondents (55.4%) had low adherence. Conclusion: The distribution of the educational booklet at the Central Buton Regional General Hospital had a positive impact on hypertensive patients' medication adherence. While there was an improvement in adherence levels, the majority of patients still exhibited low adherence after the intervention. This suggests that while educational materials are beneficial, additional strategies may be necessary to further improve adherence and control blood pressure. Keywords: Medicine Booklet, Central Buton, Hypertension, Compliance; Drug Booklet